Diagnosis dan Tatalaksana Stroke dengan Disfungsi Ereksi pada Pria Usia 50 Tahun Melalui Pendekatan Dokter Keluarga - Azelia Nusadewiarti; Vika Annisa Putri (CV. Jasa Sukses Abadi, 2020)
Stroke is a rapidly clinical signs of focal (or global) disturbance of cerebral function, with symptoms lasting 24 hours or longer or leading to death, with no cause other than of vascular origin. Stroke may cause disability and psychosocial disturbance. This study is a case report which aims to identify risk factors and clinical problems found in patients, and apply a holistic and comprehensive family doctor approach according to the problems found in patients, and conduct Evidence Based Medicine based management that is patient-centered and family focused. Primary data is obtained through history taking, physical examination and home visits. The result, Mr. UH, 50-years-old, complained left-sided limbs weakness since 2 years ago and also unable to get an erection. On the neurological clinical examination, we found parase of the left side of the limb, increase of left-sided physiological reflex, positive left-sided babinsky reflex, positive left-sided hoffman tromer, and left-sided facial nerve palsy. Uncontrolled hypertension and dyslipidemia causes stroke in these patients. In the psychosocial aspect, there is a lack of family knowledge about the patient's illness. Education and intervention are given to patients and families about stroke, prevention of other complications and treatment in 3 home visits. In the evaluation found an increase in patient compliance to avoid risk factors and family knowledge about patient care.